Ethics & issues in contemporary nursing - Burkhardt, Margaret A.; Nathaniel, Alvita K. (Australia ; Albany : Delmar Thomson Learning, 2002)
This textbook for nursing students discusses ethical issues in the nursing profession and presents a model for making decisions about these types of issues. The volume begins with a discussion of ethical theories, models, and principles from classical and contemporary philosophy
pt. 1. Guides for principled behavior. Social, philosophical, and other historical forces influencing the development of nursing -- Ethical theory -- Ethical principles -- pt. 2. Developing principled behavior. Values clarification -- Values development -- Ethical decision making -- pt. 3. Principled behavior in the professional domain. Legal issues -- Professional issues -- Professional relationship issues -- Practice issues related to technology -- Practice issues related to patient self-determination -- Scholarship issues -- pt. 4. Global issues that impinge on nursing practice. Health care changes and challenges -- Health policy issues -- Economic issues -- Social issues -- Gender issues -- Transcultural and spiritual issues -- pt. 5. The power to make a difference. Empowerment for nurses -- Enabling patient empowerment.
Includes index.
Keywords: NURSING ETHICS